2012
DOI: 10.1016/j.ehb.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disparities and the familial coexistence of child stunting and maternal overweight in guatemala

Abstract: The double burden of malnutrition, defined here as households with a stunted child and an overweight mother (SCOM), is a growing problem in Guatemala. We explored the magnitude of SCOM and the identification of socio-economic factors associated with this malnutrition duality. From the 2000 Living Standards Measurement Study from Guatemala, we obtained a sample of 2492 households with pairs of children 6–60 months and their mothers (18–49 years) and estimated the prevalence of SCOM. Economic characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 30 publications
6
89
0
11
Order By: Relevance
“…The results of this study show that the coexistence of child undernutrition and maternal overweight (characterized here as DBM) in the same household in Brazil is not as frequent as in other countries (Lee et al, ; Freire et al, ; Sarmiento et al, ). This low prevalence of DBM was found in a previous study and was expected given the very advanced stage of the nutrition transition in Brazil, where women are experiencing weight gain from one generation to the next that exceeds the height gain rate (Conde & Monteiro, ).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The results of this study show that the coexistence of child undernutrition and maternal overweight (characterized here as DBM) in the same household in Brazil is not as frequent as in other countries (Lee et al, ; Freire et al, ; Sarmiento et al, ). This low prevalence of DBM was found in a previous study and was expected given the very advanced stage of the nutrition transition in Brazil, where women are experiencing weight gain from one generation to the next that exceeds the height gain rate (Conde & Monteiro, ).…”
Section: Discussionmentioning
confidence: 55%
“…Even after controlling for covariates related to DBM, severe HFI remained as the main factor associated with DBM. Previous studies showed an association between economic variables and the existence of DBM (Lee et al, ), but the association between DBM and food insecurity had not been explored in previous studies emphasizing the innovative nature of our findings.…”
Section: Discussionmentioning
confidence: 61%
“…stunted child together with obese adults or with his/her overweight mother (13)(14)(15)(16). However, concerning undernutrition, beyond a global improvement in underweight (6), it has become apparent that several micronutrient deficiencies have not been successfully addressed until now in many LMICs, in particular iron deficiency (ID), one of the most common nutritional deficiencies in the world (17).…”
Section: Introductionmentioning
confidence: 99%
“…High prevalence of the double burden of malnutrition has been increasing in middle-and low-income countries (13) . In Guatemala, Argentina and Africa it has been shown that underweight or short stature of the child can coexist with maternal overweight (14)(15)(16) .…”
mentioning
confidence: 99%